Diagnostics and treatment of peptic ulcer: clinical guidelines of the Russian gastroenterological Association - V. T. Ivashkin; A. A. Sheptulin; I. V. Mayev; Ye. K. Baranskaya; A. S. Trukhmanov; T. L. Lapina; S. G. Burkov; A. V. Kalinin; A. V. Tkachev (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present modern concept on etiology and pathogenesis of the peptic ulcer (PUD) to general practitioners, to acquaint them with modern diagnostic methods and main treatment approaches of this disease. Summary. The PUD continues to remain one of the most widespread digestive disease. Despite a tendency to decrease of hospital admission rate of patients with uncomplicated PUD, increase in complicated forms of disease rate is noted that it is related mainly to the growing intake of non-steroidal anti-inflammatory drugs (NSAID). Helicobacter pylori infection has a leading role as PUD ethological factor. None H. pylori-associated gastroduodenal ulcers may be caused by NSAID intake or may develop within the other nosological entities (symptomatic stomach and duodenal ulcers). PUD diagnosis includes obligatory testing for H. pylori infection and carrying out eradication in the case of positive takes. At the present time the first line of antihelicobacter therapy includes standard triple clarithromycin and amoxicillin-based therapy, as well as quadrotherapy with bismuth drugs. The second line eradication therapy includes quadrotherapy with bismuth drugs and triple levofloxacin-based therapy. The third line therapy modes should be chosen after assessment of individual antibiotic sensitivity of H. pylori strains. The efficacy control of antihelicobacter treatment should be carried out not earlier than 4 weeks after the end of eradication. Conclusion. Strict conformance of diagnostic algorithm for this category of patients as well as the eradication therapy protocol allows to decrease considerably the risk of recurrence of PUD and its complications.